COMPARATIVE BETWEEN CSS FRAMEWORKS BOOTSTRAP AND BULMA FOR WEB PROJECT DEVELOPMENT - Souza, Leonardo Patrocinio; Espírito Santo, Felipe do (Revista Interface Tecnológica, 2020)
Web development is always in constant progress: developers create new tools to assist in the process of building projects for the web and there are countless tools and the most diverse purposes. This article aims to approach the CSS frameworks Bootstrap and Bulma, tools that help in the development of web projects in general. Observing the current technology, it is very important that the developer analyzes some points about this development process, such as, security, accessibility, responsiveness and, mainly, the experience that the user will have in using this application. Responsiveness is an extremely important requirement. Having an application that works well on any mobile device (cell phones, tablets, among others) is essential, as it makes access easier on these devices, making the user quickly locate their searches. Based on a bibliographic search to present the concepts of frameworks and analyze the two proposed options, it was found that there are several different characteristics in each one, however, the article highlighted the introduction to the concept, the similarities, the main resources, strengths and weaknesses. Both frameworks showed advantages and disadvantages and can be good in different web applications, but in certain points, the study demonstrated the reasons for choosing one of them.